How (Thoroughly) Does the Medium Shape Teaching? Some Considerations on Doctoral Courses in EPP at Vanvitelli University - Abbamonte, Lucia (ALLiED, 2025)
Owing to the COVID-19 pandemic, ELT teachers and their students at all levels of education were driven from the physical classroom to the remote teaching/learning dimension, and the acquisition of a new set of skills became immediately necessary. Indeed, greater trepidation lay in the increasing focus on the technology rather than the content of teaching activities, with the entailed consequences. After referring to the rich literature on teaching during the COVID-19 pandemic (Moorhouse, Kohnke 2021, 2020; Fitria 2020; Yunus, Ang, Hashim 2021; Mahib ur Rahman 2020), this study will propose some considerations on the media-channels continuum and on how their affordances shape the messages they transmit, with predictable consequences for specific teaching domains. In this light, some insights will be provided into the 2021-2022 English for Publication Purposes doctoral courses held at the Doctoral School of Humanities and Social Sciences of the Vanvitelli University.